2001
DOI: 10.1046/j.1365-2788.2001.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Abilities underlying decoding differences in children with intellectual disability

Abstract: Researchers in recent years have made much progress towards understanding why some children struggle to learn to read. However, little of this research has involved children with intellectual disability associated with an IQ < 70 (ID, also called mental retardation). In the present analysis, the authors examined cognitive similarities and differences between stronger and weaker decoders, all of whom have ID. The 65 children with ID in the present analysis were initially referred by their teachers for a study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 21 publications
(22 reference statements)
2
40
0
3
Order By: Relevance
“…The most atypical finding was the low proportion of subjects with phonological difficulties even in subjects with low IQ. This point is surprising since phonology is also associated with reading skills in subjects with mental retardation (Conners, Atwell, Rosenquist, & Sligh, 2001). Second, in subjects with normal IQ, the profile of narrative tasks was surprising as subjects had higher scores in the short but complex prose than in the long but easy one.…”
Section: Reading and Spelling Impairments In Infantile Myotonic Dystrmentioning
confidence: 98%
“…The most atypical finding was the low proportion of subjects with phonological difficulties even in subjects with low IQ. This point is surprising since phonology is also associated with reading skills in subjects with mental retardation (Conners, Atwell, Rosenquist, & Sligh, 2001). Second, in subjects with normal IQ, the profile of narrative tasks was surprising as subjects had higher scores in the short but complex prose than in the long but easy one.…”
Section: Reading and Spelling Impairments In Infantile Myotonic Dystrmentioning
confidence: 98%
“…After decades of inquiry, researchers have a strong understanding of the skills underlying decoding (Conners, Atwell, Rosenquist, & Sligh, 2001;Seymour & Evans, 1994) and of the ways to enhance decoding skills in native speakers and L2 learners (Allinder, Dunse, Brunken, & Obermiller-Krolikowski, 2001;McCandliss, Beck, Sandak, & Perfetti, 2003;Meyer & Felton, 1999). Although some English L2 learners might initially struggle with the acquisition of decoding skills, good instruction allows English L2 learners to perform at the same levels as their native English-speaking peers on decoding after a few years of explicit instruction (Chiappe, Siegel, & Gottardo, 2002;D'Anguilli, Siegel, & Maggi, 2004;Gersten & Baker, 2000;Geva, Yaghoub-Zadeh, & Schuster, 2000).…”
Section: Why Listening Comprehension?mentioning
confidence: 99%
“…Several studies have found deficits in aspects of phonological memory in children with ID compared to mental-age or skill-level matched TD children (Conners, Carr, & Willis, 1998; Henry & Winfield, 2010; Rosenquist, Conners, & Roskos-Ewoldsen, 2003; Schuchardt, Maehler, & Hasselhorn, 2011). Not surprisingly, some studies have linked phonological memory deficits with decoding ability in those with ID (Conners, Atwell, Rosenquist, & Sligh, 2001; Henry & Winfield, 2010; Numminen et al, 2000). In one study, after accounting for age, phonological memory was the only significant difference between groups of poor and good decoders with ID (Conners et al, 2001).…”
Section: Introductionmentioning
confidence: 99%